Studi Kasus Kelayakan Penerapan Sistem Hybrid Building Applied Photovoltaics (BAPV)-PLN pada Atap Gedung Politeknik Aceh - Rachmad Ikhsan; Ira Devi Sara; Rakhmad Syafutra Lubis (Universitas Syiah Kuala, 2017)
With the undeveloped BAPV(Building Applied Photovoltaics) at Office Building and Public Facilities, Caused the high price of solar modules and the lack the economic study on the use of solar modules that housed in the Banda Aceh region. Furthermore, the price of solar modules is expensive, so people think it will cost so much funds to building a BAPV’s system. These problems could be overcomed if the existing technical studies and economic studies of the application of the BAPV’s system. This study aims to assess the application of the BAPV’s system on institutions building in terms of technical and economic value, in this case the building that is used as the study object is the Polytechnic Aceh’s Building. The method that used in the technical studies are theoretical calculations and simulations using helioscope software, while the methods used for economic studies is using the methods of cost-benefit analysis (cost benefit analysis). The method used to find the NPV (Net Present Value), PP (Payback Period), IRR (Internal Rate of Return), and BCR (Benefit Cost Ratio). If the average value of solar radiation reaching 4.79 kWh / m2 / day and the average daily energy requirement is 592 kWh, the energy generated from BAPV-PLN hybrid system on the roof of the object building will reach the amount of 237 MWh/year with the capacity charge controller used is 7490 A and the capacity of the battery used is 64.487 Ah. Panel tilt angle used is 25o and the type of panel used is Monocrystalline manifold. From the economic value will obtained NPV value of Rp. 20.022.106.937, PP during 5,2 years, IRR of 36% and 3,49 of BCR. Based on the evaluation results of the feasibility study, the project of hybrid BAPV-PLN’s system on the roof of the Polytechnic Aceh’s building can be realized, because its already meet the criteria of the feasibility study to make the systems get established in real term.